Temperature mapping of fresh fish processing and different precooling methods - Styrmir Svavarsson 1992- (2020)
The focus of this study was the usage of slurry ice cooling and temporary refrigeration storage to decrease temperature of Atlantic cod in a fresh fish processing plant. Inadequate temperature control in fresh fish cold chains greatly affects product quality. It is mainly important that the cold chain remains unbroken from catch to customer. Therefore, it is desirable to cool the product down to its defined storage temperature before packaging and maintain that temperature. Ambient and fresh fish temperature in an Icelandic fish processing plant were mapped and two methods were used to decrease the temperature of the product. In the first experiment a tub with a slurry ice mixture was used and in the second a temporary refrigeration storage was used. Results from mapping the ambient and product temperature confirmed the necessity of precooling as the product was stored at temperature higher than recommended. The precooling experiments resulted in temperature profiles of the cod using different precooling methods which could be used as a guideline on how to efficiently precool fresh fish. The conclusion is that by consistently precooling the product to its intended storage temperature and maintain it through the cold chain the product quality can be increased. Markmið verkefnisins var að skoða áhrif krapaíss og tímabundinnar kæli- og frostgeymslu á hitastig í þorski í fersk fiskvinnslu. Ófullnægjandi hitastýring í fersks fisks kælikeðju hefur mikil áhrif á gæði afurðar. Það skiptir því miklu máli að kælikeðjan sé óslitin frá veiði til neytenda til að viðhalda gæðum. Því þarf að forkæla afurðina hratt og örugglega niður að geymsluhitastigi og viðhalda því. Hitastig afurðar, kælimiðils og vinnslusalar voru kortlögð og tvær forkælitilraunir framkvæmdar. Fyrri tilraunin gekk út á að setja þorskhnakka í ker með krapaís og sú síðari gekk út á að geyma fullunna afurð í pakkningu inn í kæli og frysti. Niðurstöður sýndu að hitastigið í afurðinni þegar henni er pakkað var of hátt miðað við ráðlagt geymsluhitastig fersks ...